Per Capita Income and the Demand for Skills - Justin Caron; Thibault Fally; James R. Markusen (Center for Economic Studies and ifo Institute (CESifo), 2017)
Almost all of the literature about the growth of income inequality and the relationship between skilled and unskilled wages approaches the issue from the production side of general equilibrium (skill-biased technical change, international trade). Here, we add a role for income-dependent demand interacted with factor intensities in production. We explore how income growth and trade liberalization inuence the demand for skilled labor when preferences are non-homothetic and income-elastic goods are more intensive in skilled labor, an empirical regularity documented in Caron, Fally and Markusen (2014). In one experiment, counterfactual simulations show that sectorneutral productivity growth, which generates shifts in consumption towards skill-intensive goods, leads to significant increases in the skill premium: in developing countries, a one percent increase in productivity leads to a 0.1 to 0.25 percent increase in the skill premium. In several countries, including China and India, simulations suggest that the historical growth experienced in the last 25 years may have led to an increase in the skill premium of more than 10%. In a second experiment, we show that trade cost reductions generate quantitatively very different outcomes once we account for non-homothetic preferences. These imply substantially less predicted net factor content of trade and allow for a shift in consumption patterns caused by trade-induced income growth. Overall, the negative effect of trade cost reductions on the skill premium predicted for developing countries under homothetic preferences (Stolper-Samuelson) is strongly mitigated, and sometimes reversed.
Keywords: F10; O10; F16; J31; 330; non-homothetic preferences; skill premium; per capita income; internatonal trade